Analisis Keefektifan Penerapan Sistem Informasi Akuntansi Pada Usaha Mikro Kecil dan Menengah - Septrita Sutriyani; Tri Inda Fadhila Rahma; Aqwa Naser Daulay (Jurnal Riset Ekonomi dan Akuntansi, 2024)
The effectiveness of the application of accounting information systems can make it easier for MSME players to make financial records and can make it easier to search and find the information needed. This study aims to determine the application of accounting information systems manually and to determine the application of accounting information systems by computer and see the effectiveness of the application of accounting information systems in MSMEs Almaany Kitchen Binjai. This research uses a qualitative descriptive approach method. The subject of this research is the owner of UMKM Almaany Kitchen. The object of this research is the Financial Statements in the form of cash income and expenses in 2022. The data analysis technique uses indicators of the effectiveness of the Accounting Information System Implementation. Data collection techniques are interviews and documentation. The application used in this computer application is Microsoft Excel 2016. The results of this study indicate that the application of computerized Accounting Information Systems is more effective than manual use because judging from these eight indicators only seven are effective, namely data security, time, accuracy, relevance, physical comfort, information quality and information technology with an effectiveness level of 87.5%, while the ineffective indicator is the variety of reports, this is due to the lack of understanding of MSME owners Almaany Kitchen about accounting standards.